Student Mathematical Communication Ability Viewed from Self-Confidence in the ARIAS Model Nuanced Ethnomathematics - Nurhaqiqi Noviyana, Ika; Rochmad, Rochmad; Dewi (Nino Adhi), Nuriana Rachmani (Universitas Negeri Semarang, 2020)
This study aims to (1) find out whether the mathematical communication abilities of students in ethnomathematics-nuanced ARIAS learning can reach the actual completeness limit, and (2) describe students' mathematical communication abilities based on self-confidence in ARIAS learning with nuanced mathematics. This study uses a mixed-method with sequential explanatory type. The population of this study is class VIII of Junior High School 1 Karangampel 2018/2019. The research subjects were selected based on self-confidence categories, namely high, medium, and low. Data collection techniques used tests of mathematical communication abilities, self-confidence questionnaires, and interviews. The results showed that (1) students in the class with ethnomathematics ARIAS learning had reached the actual completeness limit, and (2) the description of students' mathematical communication abilities in the high self-confidence category, moderate self-confidence and low self-confidence had the same able to listen, discuss, and write about mathematics, all three are also able to read with an understanding of a written presentation, but have not been able to formulate a definition, for students with moderate self-confidence and low self-confidence also have the same that is able to express objects - real objects, situations, and everyday events in the form of mathematical models (images, tables, diagrams, graphs, algebraic expressions) and able to make mathematical questions according to the information contained in the questions, and only students in self-confidence are who is able to explain mathematical ideas and models into ordinary languages.